2022
DOI: 10.1038/s41390-022-02163-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on human ACE2 and ACE2-expressing alveolar type II cells levels

Abstract: Background Angiotensin-converting enzyme 2 (ACE2) is the receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which causes COVID-19. Viral entry requires ACE2 and transmembrane protease serine 2 (TMPRSS2). Transcriptomic studies showed that children display lower ACE2 than adults, though gene expression levels do not always correlate with protein levels. We investigated the effect of age on ACE2 and TMPRSS2 protein expression in alveolar type II (AT2) cells in the lungs of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
8
0
4
Order By: Relevance
“…Non-ventilated individuals did not demonstrate these changes in type II pneumocytes and experienced no such age-related increase in expression [ 30 ]. Silva et al demonstrated similar findings in type II pneumocytes and consequently identified that angiotensin II levels in children were higher than those in adults [ 31 ]. Ang-(1–7)/Ang II ratios served as surrogate markers for ACE2 activity in this study and were higher in adults [ 31 ].…”
Section: Demographic Characteristicsmentioning
confidence: 73%
See 1 more Smart Citation
“…Non-ventilated individuals did not demonstrate these changes in type II pneumocytes and experienced no such age-related increase in expression [ 30 ]. Silva et al demonstrated similar findings in type II pneumocytes and consequently identified that angiotensin II levels in children were higher than those in adults [ 31 ]. Ang-(1–7)/Ang II ratios served as surrogate markers for ACE2 activity in this study and were higher in adults [ 31 ].…”
Section: Demographic Characteristicsmentioning
confidence: 73%
“…Silva et al demonstrated similar findings in type II pneumocytes and consequently identified that angiotensin II levels in children were higher than those in adults [ 31 ]. Ang-(1–7)/Ang II ratios served as surrogate markers for ACE2 activity in this study and were higher in adults [ 31 ].…”
Section: Demographic Characteristicsmentioning
confidence: 73%
“…Whereas in some studies no differences in SARS-CoV-2 RNA loads between children and adults were found (75, 76), others reported slightly lower viral RNA loads in children (77, 78). ACE2 expression was shown to be age-dependent in the nasal epithelium (79) as well as in alveolar type 2 cells (80), with lower expression in children compared to adults. However, our study focused on lung tissue from adult donors and didn’t include younger adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, clinical records showed that people in younger age are less likely to develop severe symptoms when infected 5,49 . This may be partially due to the fact that pulmonary epthelia in younger people express less viral receptors [50][51][52] . Blocking these receptors can achieve much lower infection rate 40,53,54 .…”
Section: Discussionmentioning
confidence: 99%